Causal effects and immune cell mediators between prescription analgesic use and risk of infectious diseases: a Mendelian randomization study - Jin, Yi; Yu, Xinghao; Li, Jun; Su, Mingzhu; Li, Xiaomin (Frontiers in Immunology, 2023)
Clinical observations have found that prolonged use of analgesics increases the incidence of infection. However, the direct causal relationship between prescription analgesic use (PAU) and risk of infection (ROI) remains unclear.This study used Mendelian randomization (MR) design to estimate the causal effect of PAU on ROI, as well as their mediating factors.Genetic data on prescription analgesics use and immune cells were obtained from published GWAS. Additionally, data on ROI were extracted from the FinnGen data base.Two-sample Mendelian randomization analysis and Multivariate MR (MVMR) analysis were performed using inverse variance weighting (IVW) to ascertain the causal association between PAU and ROI. Finally, 731 immune cell phenotypes were analyzed for their mediating role between analgesics and infection.Using TwoSample MR,IVW modelling showed that genetically predicted opioids use was associated with increased risk of pulmonary infection(PI) (OR = 1.13, 95% CI: 1.05-1.21, P < 0.001) and upper respiratory infection (URI) (OR = 1.18, 95% CI: 1.08-1.30, P < 0.001); NSAIDs was related to increased risk of skin and subcutaneous tissue infection (OR = 1.21, 95% CI: 1.05-1.39, P = 0.007); and antimigraine preparations was linked to a reduced risk of virus hepatitis (OR = 0.79, 95% CI: 0.69-0.91, P < 0.001). In MVMR, the association of opioids with URI and PI remained after accounting for cancer conditions. Even with a stricter threshold (P < 0.05/30), we found a significant causal association between opioids and respiratory infections (URI/PI). Finally, mediation analyses found that analgesics influence the risk of infection through different phenotypes of immune cells as mediators.This MR study provides new genetic evidence for the causal relationship between PAU and ROI and the mediating role of immune cells was demonstrated.